Placental site trophoblastic tumor during pregnancy complicated by uterine rupture - A. N. Sulima; D. A. Beglitse; A. A. Davydova; V. V. Voronaya; A. N. Rybalka; P. N. Baskakov (Акушерство, гинекология и репродукция)
The placental site trophoblastic tumor is a rare highly malignant form of trophoblastic disease, which occurs in as few as 0.4-2.0 % of all trophoblastic tumors. Available publications describes not more than 200 clinical cases of this pathology often affecting patients of reproductive age, thereby underscoring special importance of its diagnostics and treatment. Here we describe the rare clinical case of spontaneous uterine rupture in pregnant woman at 26 weeks of gestation carrying placental site trophoblastic tumor, previously undescribed in research literature. The complexity of diagnosing such pathology that resulted in antenatal fetal death and hysterectomy is demonstrated.